GAMBARAN PENCAPAIAN PERKEMBANGAN ANAK DI PAUD PEMBINA KELURAHAN LEKOBALO - Ritna Rahman; Dewi Modjo; Andi Akifa Sudirman (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2023)
Growth occurs from an early age to adulthood. The Progress cannot be measured, but it can be felt. Growth is progressive, systematic and continuous. The objective of research is to overview the achievement of child growth. This type of quantitative research with a descriptive research design. The total population is 33 children, the sampling technique uses total sampling where the total population is equal to the number of samples. The results showed there were 13 people who had appropriate developmental achievements, 19 people had doubtful developmental achievements, and 1 person had possible deviations from developmental achievements. Therefore it concluded most of the children in PAUD Pembina of Lekabalo district have dubious developmental achievements of 19 people. Suggestions for parents to deeply pay attention to the children growth at every age. For the school to help or provide stimulation to children to achieve child growth according to the child's age because the growth according to age is very important for children.